(untitled) (Eurasian Journal of Engineering and Technology, 2024)
Rusafa, often referred to as Al-Rusafa, is one of the nine administrative districts in Baghdad, Iraq. The site is located on the eastern side of the Tigris River, with Al-Karkh situated on the opposite western side. The Rusafa side, located in the heart of Baghdad, Iraq’s capital, is a prominent sector that has been part of the city since ancient times. The Tigris River separates it from Karkh, which comprises the city’s essential components. Figure 1 depicts the precise geographical location of Al Rusafa